Theoretical Investigation of the Biogenetic Pathway for Formation of Antibacterial Indole Alkaloids from Voacanga africana - FINDIK, VOLKAN (My University, 2022)
The energetic viability of the previously proposed biogenetic pathway for the formation of two unique monoterpenoid indole alkaloids, voacafricine A and B, which are present in the fruits of Voacanga africana, was investigated using density functional theory computations. The results of these calculations indicate that not only is the previously suggested pathway not energetically viable but also that an alternative biosynthetic precursor is likely.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences